History and Myth in Pictorial Narratives of the Russian 'Patriotic War', 1812-1914 - Nedd, Andrew M. (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XIII, 273 p. 59 illus., 45 illus. in color.